Resolution of (R, S)‐1‐(4‐methoxyphenyl)ethanol by lipase‐catalyzed stereoselective transesterification and the process optimization. Issue 2 (14th December 2021) - He, Bingbing; Tang, Fengci; Sun, Chenrui; Su, Jiahao; Wu, Bingcheng; Chen, Yan; Xiao, Yuquan; Zhang, Panliang; Tang, Kewen
Abstract: An efficient lipase‐catalyzed stereoselective transesterification reaction system was established for resolution of 1‐(4‐methoxyphenyl)ethanol (MOPE) enantiomers. A series of lipases were tested and compared. The immobilized lipase Novozym 40086 is selected as the best choice. The effects of organic solvent, acyl donor, time and temperature on substrate conversion ( c ), and optical purity of the remaining substrate ( ee S ) were investigated. Response surface methodology and central composite design were employed to evaluate the effect of some important factors and to optimize the process. Under the optimized conditions including solvent of n ‐hexane, acyl donor of vinyl acetate, temperature of 35°C, substrate molar ratio of 1:6, enzyme dosage of 20 mg, and reaction time of 2.5 h, ee S of 99.87% with c of 56.71% is achieved. The use of alkane solvent and immobilized enzyme, the mild reaction conditions, and the reduced reaction time make the system promising in industrial application. Abstract :